Chromatography-free "two-pots" asymmetric total synthesis of (+)-sesamin and (+)-aschantin. Issue 40 (2nd October 2020) - Hajra, Saumen; Garai, Sujay; Sen, Biswajit
Abstract: A gram-scale chromatography-free asymmetric total synthesis of both homo- and heterobiaryl furofuran lignans containing at least one methylenedioxy phenyl unit such as (+)-sesamin and (+)-aschantin is accomplished in "two-pots" from easily accessible enantiopure lactone involving four steps in high overall yields. Steps- and pot economy are the key advantages of the protocol. Additionally, the bromo-functionality of the intermediates is useful for late stage functionalization. Graphical abstract: Image 1 Highlights: Chromatography-free total synthesis. Two-pots total synthesis – It reduces the amounts of solvent, waste, time, labor and the cost. Asymmetric total synthesis of furofuran lignans – sesamin, aschantin and their analogues for late stage functionalization.